Impacto da distância de lojas físicas nas vendas diretas do e-commerce - Silva, Ricardo Ribeiro (2019)
The main objective from this study is to analyzethe correlation between the client distance from a physical store and his volume of purchases in their ecommerce from an underwear brand. The presence of moderator elements between them were also studied (customer age and monthly wage).To achieve the results, this study is going to use a simple linear regression based on the enterprise data acquired and used in this study processed with geomarketing tools. As a result, it was obtained the existence of a negative correlation between the consumer distance to a physical store and the medium volume or purchases in the online store. It was also possible to show that the relation between the medium number of purchases and the distance of the consumer to a physical store has a potency rule, which was possible to extract a relation coefficient between distance and purchase volume. According to the study results, this negative relation was observed as a result from the enterprise brand memory caused by the proximity of the customer towards a store. This study expand the omni-channel literature and also allows managers to apply this model to their marketing expansion strategy in order to have quantitative data about where to expand the brand.